STRATEGI PENGEMBANGAN KEGIATAN KEAGAMAAN ANAK USIA DINI DI TK HARAPAN IBU TANAH MAS BANYUASIN - Nyimas Nurrohmah (El-Ghiroh : Jurnal Studi Keislaman, 2017)
this scholarly work discusses the efforts of the school in realizing the generation of character by way of introducing religious activities gradually to learners. The method of this research is the type of research phenomenology, using qualitative descriptive approach, with sabjek research is the head teacher of the classroom teachers and guardians of students. In this case the data collection is done by observation, interview, and documentation. Data analysis technique using Model Miles and Humberman approach. The study found that first, the kindergarten strategy in developing early childhood religious activities in Harapan Ibu Tanah Banyuasin Kindergarten was pursued by establishing the development of the religious activities of the AUD that it wanted to be internalized, establishing its assessment form, planning daily habituation along with its religious activity programs, applying development of religious activities, awaken to all teachers of the important role and responsibility in achieving the goal of developing religious activities in early childhood, as well as cooperating with the guardian of students in the development of early childhood religious activities in the kindergarten.